BALI CALF PRAESEN STATUS - Sari, Sayu Raka Padma Wulan; Suartha, I Nyoman; Batan, I Wayan (Buletin Veteriner Udayana, 2016)
This study aims were to inventory the profile of bali calf praesen status. Praesen status examination includes body temperature, respiration, heartbeat, and arterial pulse. This study used 15 bali calf with the age group of four months as much as five, aged five months as much as five,and aged six months as much as five. Praesen status measurement performed in the morning,afternoon, and evening. The results of the research praesen status of bali calf held in Bali Cattle Breeding Center, Sobangan, Mengwi, Badung is the average body temperature of calves aged fourmonths 38.80 ± 0.20°C, aged five months of 38.60 ± 0.53°C, aged six months 38.47 ± 0.42°C. The average frequency of respiration calf aged four months 45.60 ± 3.27 times/min, aged five months31.67 ± 5.31 times/min, aged six months  37.93 ± 10.25 times/min. The average frequency of arterial pulse calf aged four months 93.40 ± 5.55 times/min, aged five months 82.80 ± 2.55 times/min, aged six months 82.40±8.49 times/min. The average frequency of the heartbeat calfaged four months 91.73 ± 4.39 times/min, aged five months 83.20 ± 3.50 times/min, aged sixmonths 83.40 ± 8.86 times/min. Based on the research results bali calf (4-6 months) it can be concluded that: body temperature was 38.62±0.17°C; respiration frequency was 38.40 ± 6.98 times/min; arterial pulse frequency was 86.20±6.24 times/min; and heart beat frequency was 86.11± 4.87 times/min. Praesen status is expected to be used as a reference for bali calf health examination.
Keywords: bali cattle; calf; praesen status